Interpersonal Communication and Schizophrenia: Challenges and Barriers to Recovery - Rahmi Aini (SEAN Institute, 2024)
Interpersonal or interpersonal communication is communication between two or more people face to face which allows each participant to capture other people's reactions directly, both verbally and non-verbally. Interpersonal communication in question is a process of conveying carried out by a psychologist to patients suffering from the mental disorder Schizophrenia where the process of conveying messages is carried out directly or face to face so that the communicator and the communicant messages can interact with each other. directly , so that both get the same understanding and understand each other in depth. The research chosen by the researcher is descriptive research with a qualitative approach. The aim of this research is to find out how interpersonal communication patterns are carried out by psychologists and what challenges there are in the recovery process. So the research results state that, in communicating with schizophrenic patients, a psychologist needs to create a safe, comfortable and conducive situation to create good rapport. Apart from that, psychologists in carrying out interpersonal communication with schizophrenic patients need to understand communication ethics and have a high sense of empathy. Psychologists need to really understand how to communicate with schizophrenic patients based on the type of schizophrenia experienced by the patient. The response given by the psychologist as the comic actor really needs to make the schizophrenic patient feel safe and comfortable, so that by creating a relaxed, safe, comfortable and conducive atmosphere it will help in the patient's mental recovery process.